IDENTIFIKASI KELURUSAN STRUKTUR GEOLOGI DI SEKITAR SESAR GARSELA, JAWA BARAT - Rangkuti, Nazla Syafitri; Zahara, Amelia; Azmi, Nurul (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
The West Java region contains several basins that have been studied for resource and disaster-related purposes, one of which is located in the southern part of the Bandung Basin. The southern area of the Bandung Basin falls within the Quaternary Volcanic Zone and the Southern Mountain Zone. The Garsela Fault is an active fault that stretches from southern Garut to southern Bandung. This study aims to observe structural lineaments around the Garsela Fault in southern Garut. The data used includes DEMNAS imagery and geological maps. The use of hill shading techniques produces three-dimensional shadows and allows for manual extraction of lineaments. More structural lineaments were identified due to the rugged mountainous morphology with Tertiary-aged lithological formations. The identified lineaments predominantly trend northeast–southwest. north–south, east–west, and some northwest–southeast. The northeast–southwest direction is the dominant structural orientation in southern Garut, aligning with the orientation of the Garsela Fault. The use of this imagery can serve as an initial step for further research in identifying geological structural lineaments.